Jackfruit Waste: A Promising Source of Food and Feed (Annals of Bangladesh Agriculture, 2020)
All the food sources comprise edible and non-edible waste portions. With increasing demand for food and feed the current agriculture is focusing on agro-processing to utilize the maximum portion of the plant or animal resources. This review paper aims at summarizing the present status of utilization of jackfruit (Artocarpus heterophyllus Lam, Moraceae) wastes in food, feed, and other industry. Apart from the non-edible portion like peel and axis, the edible by-products like seeds of jackfruit mostly remain underutilized worldwide including Bangladesh. This article has reviewed the works devoted to utilize different waste portions of jackfruit other than the juicy edible bulbs. There are many works which suggested that the thick peel of jackfruit can be utilized in nutrient enriched cattle feeds, extraction of bio-fuel, nano-porous adsorbent for removing dye etc. The peel and central axis of this fruit also had investigated for extraction of pectin. The seeds of jackfruit were attempted by many researches to be used in various bakery products. The starch and protein fractions were isolated from jackfruit seeds flour to make them use at a purified state in the food formulations.Ann. Bangladesh Agric. (2019) 23(1) : 91-102